The Effect of Marketing Mix On “KPR Xtra Bebas” Decision Making in Bank X Regional I - Kevin Michael Arthur; Alla Asmara; Megawati Simanjuntak (Department of Family and Consumer Sciences, Faculty of Social and Human Ecology, IPB University, 2019)
The rapid growth of mortgages affected Bank X to launch product innovation